ARID1A Deficiency Is Associated With High Programmed Death Ligand 1 Expression in Hepatocellular Carcinoma. Issue 4 (30th December 2020) - Iseda, Norifumi; Itoh, Shinji; Yoshizumi, Tomoharu; Yugawa, Kyohei; Morinaga, Akinari; Tomiyama, Takahiro; Toshima, Takeo; Kohashi, Kenichi; Oda, Yoshinao; Mori, Masaki
Abstract : The clinicopathological features of carcinomas expressing AT‐rich interaction domain 1a (ARID1A) and programmed death ligand 1 (PD‐L1) in HCC are poorly understood. Here, we examined ARID1A and PD‐L1 expression in surgically resected primary hepatocellular carcinoma (HCC) and the association of ARID1A and PD‐L1 expression with clinicopathological features and patient outcomes. Their association with ARID1A expression and tumor‐associated CD68‐positive macrophage was further explored. Using a database of 255 patients who underwent hepatic resection for HCC, immunohistochemical staining of ARID1A, PD‐L1, and CD68 was performed. We also analyzed the expression PD‐L1 after ARID1A knockdown in HCC cell lines. Samples from 81 patients (31.7%) were negative for ARID1A. Negative ARID1A expression was significantly associated with male sex, high alpha‐fetoprotein, high des‐gamma‐carboxyprothrombin, large tumor size, high rate of poor differentiation, microscopic intrahepatic metastasis, and PD‐L1 expression. In addition, negative ARID1A expression was an independent predictor for recurrence‐free survival, overall survival, and positive PD‐L1 expression. Stratification based on ARID1A and PD‐L1 expression in cancer cells was also significantly associated with unfavorable outcomes. PD‐L1 protein expression levels were increased through phosphoinositide 3‐kinase/AKT signaling after ARID1A knockdown in HCC cells. HCC with ARID1A‐low expression was significantly correlated with high levels of tumor‐associated CD68‐positive macrophage. Conclusion: Our large cohort study showed that ARID1A expression in cancer cells was associated with a poor clinical outcome in patients with HCC, PD‐L1 expression in cancer cells, and tumor microenvironment. Therefore, ARID1A may be a potential molecular biomarker for the selection of patients with HCC for anti‐programmed death 1/PD‐L1 antibody therapy. Abstract :